The relationship between the first episode of wheezing and matrix metalloproteinases-9 and MMP-2 and tissue inhibitors of MMP-1 levels in preterm infants - Rabia Gonul Sezer; Gokhan Aydemir; Abdulkadir Bozaykut; Serdar Hira; Ilhan Asya Tanju; Ömer Özcan (Annals of Thoracic Medicine, 2013)
Aims: Matrix metalloproteinases (MMP) have been associated with neonatal lung morbidity and MMP dysregulation contributes to the pathology of chronic and acute lung disorders. Most of the previous studies were performed in the 1 st weeks of life of the preterm newborns. There are no data on the serum levels of MMP-2, MMP-9 or tissue inhibitors of matrix metalloproteinases (TIMP-1) from preterm infants recovering from lung morbidities. We aimed to compare MMP-2, MMP-9 and TIMP-1 levels in preterm and term infants hospitalized with their first episode of wheezing. Methods: We prospectively evaluated 18 preterm infants with a history of chronic lung disease, respiratory distress syndrome or oxygen therapy and 14 age- and sex-matched term infants who were admitted for a first episode of wheezing. We quantified total serum concentrations of MMP-2, MMP-9 and TIMP-1 to assess whether these serum markers levels were associated with the first episode of wheezing in infants with a history of oxygen therapy during the neonatal period. Results: Upon hospitalization, MMP-2 and TIMP-1 levels were higher in preterm infants than in term infants. In contrast, there was no significant relationship between MMP-9 levels or the MMP-9/TIMP-1 ratio between preterm and term infants. The area under the receiver operating characteristic curve for MMP-2 was 0.70 (95% confidence interval [CI] 0.51-0.89). The area under the curve for TIMP-1 was 0.78 (95% CI 0.61-0.94). MMP-9, MMP-2 and TIMP-1 levels did not correlate with gestational age, gender or severity of wheezing. Conclusion: The negative proportion of MMP-9 to TIMP-1 that we detected in term infants was not present in preterm infants. The balance of MMP-9 to TIMP-1 may have been disrupted by lung damage in the premature infants. Overproduction of MMP-2 and TIMP-1 in the serum may be associated with the pathogenesis of wheezing in preterm infants.